PENGARUH MOTIVASI BERPRESTASI DAN KEBIASAAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA - Yuliany, Nur; Ulfiani Rahman; Amriani (Al asma : Journal of Islamic Education, 2022)
This study discusses the mathematics learning achievement of students which is influenced by achievement motivation and study habits. Learning achievement is an indicator of the quality and quantity of knowledge that students have known. The purpose of this study was to determine the effect of achievement motivation and study habits on mathematics learning achievement of eighth grade students of SMP DDI Al-Irsyad Rampegading Makassar. This study uses a quantitative approach with the type of Ex-Post Facto research. The population in this study were students of class VIII SMP DDI Al-Irsyad Rampegading Makassar, totaling 100 students. Sampling using simple random sampling technique with a sample size of 50 students. There are two data collection techniques used, namely a questionnaire (questionnaire) to see the level of achievement motivation and student study habits and documentation to see mathematics learning achievement. The analysis technique uses multiple linear regression. Based on the results of data analysis using descriptive statistics for achievement motivation is in the medium category with an average value of 72.74, for study habits is in the medium category with an average value of 75.08, and for students’ mathematics learning achievement is in the medium category with the average value is 82.08. The results of inferential statistical analysis showed that achievement motivation had a positive and significant effect on learning achievement in mathematics. Study habits have a positive and significant effect on learning achievement in mathematics and achievement motivation and study habits have a positive and significant effect so that study habits and achievement motivation help students to obtain good learning outcomes.